2014
DOI: 10.1186/1475-2875-13-252
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication with anti-malarials is a common practice in rural communities of Kilosa district in Tanzania despite the reported decline of malaria

Abstract: BackgroundSelf-medication has been widely practiced worldwide particularly in developing countries including Tanzania. In sub-Saharan Africa high incidences of malaria have contributed to self-medication with anti-malarial drugs. In recent years, there has been a gain in malaria control, which has led to decreased malaria transmission, morbidity and mortality. Therefore, understanding the patterns of self-medication during this period when most instances of fever are presumed to be due to non-malaria febrile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 30 publications
5
84
2
3
Order By: Relevance
“…Despite the limited data on self-and OTC medications in Tanzania, the current available data on SM and OTC in Tanzania have focused mainly on malaria and fever-related illnesses [5][6][7] . In all these cases, SM and OTC medications were found to be very common practices among interviewed participants.…”
Section: Short Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limited data on self-and OTC medications in Tanzania, the current available data on SM and OTC in Tanzania have focused mainly on malaria and fever-related illnesses [5][6][7] . In all these cases, SM and OTC medications were found to be very common practices among interviewed participants.…”
Section: Short Communicationsmentioning
confidence: 99%
“…Previous studies from subSaharan Africa with different study population and with specific types of morbidities found higher prevalence (over 70%) of SM [14][15][16] . Furthermore, in one rural area of Tanzania, a recent qualitative study suggested SM practices to be common [5] . Therefore, the prevalence of SM in this study is within the expected limits.…”
Section: Short Communicationsmentioning
confidence: 99%
“…The greatest burden is in tropical regions, and in Africa, malaria remains one of the most common diagnoses . For many years, malaria has been a leading cause of death in sub‐Saharan Africa especially among children, although the number of deaths is decreasing, helped by the availability of rapid diagnostic tests, prevention programmes and antimalarial medicines . Malaria also has a significant impact on morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, malaria is one of the leading public health concerns in infected countries, causing up to 660 000 deaths per year or higher . Malaria is also a public health concern in Tanzania where in 2000, malaria accounted for over 43% of outpatient attendance, 42% of all hospital admissions and 32% of hospital deaths, with a similar situation in Uganda . The prevalence of confirmed malaria in children under five in Tanzania using a rapid diagnostic test (mRDT) in 2011–2012 was 9% .…”
Section: Introductionmentioning
confidence: 99%
“…Most community members in malaria endemic countries, including Tanzania lack the correct knowledge about the causes of febrile illnesses and most have the notion that fever and malaria are synonymous and quite often used interchangeably [30,54]; therefore even at a time that malaria has remarkably declined, malaria is still perceived to be a much more common cause of fever [12,13,61,62]. Due to lack of knowledge, most clients expect a positive malaria test and when given negative results, sometimes they may not accept them and would put pressure on the prescriber to consider a diagnosis of malaria [63], and if the prescriber do not concur they may resort to self-medication with antimalarial drugs [64,65].…”
Section: Challenges From Clients' Perspectivesmentioning
confidence: 99%